Correlation between imaging and tissue biomarkers of hypoxia in squamous cell cancer of the head and neck - Kunder, Shreya; Chatterjee, Abhishek; Manna, Subhakankha; Mahimkar, Manoj; Patil, Asawari; Rangarajan, Venkatesh; Budrukkar, Ashwini; Ghosh-Laskar, Sarbani; Agarwal, Jai Prakash; Gupta, Tejpal (World Journal of Nuclear Medicine, 2021)
The aim of this study was to correlate endogenous tissue biomarkers of hypoxia with quantitative imaging parameters derived from 18F-fluoro-misonidazole (F-MISO) and 18F-fluoro-deoxy-glucose (FDG) positron emission tomography/computed tomography (PET/CT) and clinical outcomes in locoregionally advanced head and neck squamous cell carcinoma (HNSCC). Tumor-tissue blocks of HNSCC patients with pretreatment F-MISO-PET/CT and FDG-PET/CT were de-archived for expression of hypoxia-inducible factor-1 alpha (HIF-1α) subunit, carbonic anhydrase-IX (CA-IX), and glucose transporter subunit-1 (GLUT-1) using immunohistochemistry (IHC). The intensity of staining was graded and correlated with quantitative imaging parameters and with disease-related outcomes. Tissue blocks were analyzed for 14 of 20 patients. On IHC, median H-scores for HIF-1α, CA-IX, and GLUT-1 were 130, 0, and 95, respectively. No significant correlation of tissue biomarkers of hypoxia with quantitative imaging parameters was found. However, borderline significant correlation was seen for H-scores of CA-IX with hypoxic tumor volume (HTV) (r = 0.873, P = 0.054) and fractional hypoxic volume (r = 0.824, P = 0.086) derived from F-MISO-PET/CT. At a median follow-up of 43 months, 5-year Kaplan–Meier estimates of locoregional control, disease-free survival, and overall survival were 53%, 43%, and 40%, respectively. Increased expression of HIF-1α or GLUT-1 (dichotomized by median H-scores) was not individually associated with disease-related outcomes. However, a combination of high HTV (>4.89cc) with above median H-scores of either HIF-1α (>130) and/or GLUT-1 (>95) was associated with worse clinical outcomes. None of the three patients with such “adverse hypoxic profile” were long-term survivors. There is no significant correlation of endogenous tissue biomarkers of hypoxia (HIF-1α, CA-IX, and GLUT-1) with quantitative imaging parameters (on F-MISO-PET/CT and FDG-PET/CT) or long-term outcomes in HNSCC. However, a combination of both can identify a subgroup of patients with adverse outcomes.
Keywords: And imaging; biomarkers; head–neck cancer; hypoxia; immunohistochemistry